ChatGPT? What is all this hype about? / Assoc. Prof. Dr Angeline Ranjethamoney Vijayarajoo - Ranjethamoney Vijayarajoo, Angeline (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Since the release of ChatGPT, there is much being said about how this can enhance student learning and how teaching staff can adapt their teaching and assessment to embrace this new AI. Having said all this, the fact remains that there has been less said in terms of academic literature published on ChatGPT. This article reviews some work done on ChatGPT, in the area of education, specifically, in four countries -Australia, New Zealand, the United States and the United Kingdom. The themes covered by the article include academic integrity and the voice of students. The author focusses on these two aspects, being a member of an academic institution in Malaysia. However, there is still much research that needs to go into these areas before more findings and better ways of managing AI can be achieved.